Modeling metal forming of a magnesium alloy using an adapted material model. Issue 7 (13th June 2022) - Wolf, Alexander; Küsters, Niklas; Bräunling, Sven; Weck, Daniel; Kittner, Kristina; Gude, Maik; Prahl, Ulrich; Brosius, Alexander
Abstract: Modeling sheet metal forming of materials for lightweight construction requires an understanding of their plastic behavior in different loading directions. The presented work focuses on twin‐roll‐casted magnesium alloy AZ31. It is characterized by unique mechanical properties compared to other magnesium alloys due to the employed twin‐roll‐casting‐process. In general, magnesium alloys with their hexagonal closed‐packed structure possess a complex forming behavior including a deformation‐induced anisotropy evolution. In the context of a fast design approach, an adaptation of the Yield2000‐2d criteria usually used for body‐centered cubic or face‐centered cubic materials is tested. The goal is a simple, versatile material model which parameters are determined just by tensile tests with moderate testing effort. In the investigated model, the yield locus definition is modified by adding a term for the yield exponent evolution during the forming process. The modeling approach is presented and the necessary tests for material data acquisition and evaluation are described. After experimental identification of the model parameters, the material model is applied in a forming simulation. The investigation provides promising results matching well with experimental data. Thus, the application of this model in a fast design step is feasible, offering valuable data like deformed shape, process‐related material properties and induced stresses for further processing.